Analysis of Rice Stock Control to Ensure Availability of Food Logistics: A Case Study of Perum Bulog in Tembe Village, North Rarowatu District, Bombana Regency - Ismail Ismail; La Rianda; Sakir Sakir (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2021)
This study aims to determine the flow of rice procurement at the Bulog Tembe Public Corporation and analyze the rice stock supply system at Bulog Tembe Public Corporation, North Rarowatu District, Bombana Regency, in ensuring the availability of food logistics in 2021-2025. Determination of the research location is done purposively. The data was collected using observation, interviews, literature, and documentation. The analysis used is forecasting, minimum rice procurement (economic order quantity), safety stock, full inventory, and reorder point. Based on the results of forecasting analysis at Perum Bulog Tembe, North Rarowatu District, for planning and controlling rice supplies in 2021-2025. The minimum quantity of rice procurement (Economic Order Quantity) at Perum Bulog Tembe in 2021 is 33.70 tons; in 2022, it is 36.93 tons; in 2023, it is 39.87 tons; in 2024, it is 43.04 tons; and in 2025, 45.95 Tons. Total Safety Stock at Perum Bulog Tembe in 2021 is 936 tons; in 2022, it is 1,071 tons; in 2023, it is 1,206 tons; in 2024, it is 1,341. In 2025, it is 1,476 tons. The Maximum Inventory at Perum Bulog Tembe in 2021 is 969.70 tons; in 2022, it is 1,107.93 tons; in 2023, it is 1,245.87 tons; in 2024, it is 1,384.04 tons; and in 2025, it is 1,521 .95 Tons. The number of reorder points at Perum Bulog Tembe in 2021 is 1,090 tons; in 2022, it is 1,247 tons; in 2023, it is 1,404 tons; in 2024, it is 1,561 tons; in 2025, it is 1,719 tons.